Interaction of silica with polystyrene: mechanical properties, polymer/filler adhesion and failure behavior - Selvin P. Thomas (Chimica Techno Acta)
Composites of polystyrene with different loading of silica were prepared by melt mixing in a Brabender Plasticorder at a rotor speed of 60 rpm. The mechanical properties of the composites such as tensile behavior, impact strength, and flexural properties were studied as a function of filler loading. The tensile moduli of the composites increased with silica content. To improve adhesion between the filler and the matrix, an amino silane coupling agent was used. The composites with coupling agents showed enhanced mechanical properties. Thermal properties were measured using differential scanning calorimetry (DSC), thermogravimetry (TGA) and flammability tests. Composites with 15 wt.% and 0.5 wt.% coupling agent showed optimum properties. Scanning electron microscopy (SEM) studies of the tensile fractured samples revealed the extent of filler dispersion and filler/matrix interaction. Finally, experimental results were compared with theoretical predictions.